Use of OASIS as a library software package at the Brent International School (BIS) a study - Javier, Jean Paul C. (1999)
This is a study on the use of OASIS as a library Software Package at the Brent International School. Specifically it aims: 1) to find out how the BIS library staff are coping with the computerization of the BIS library, 2) to determine the advantages and disadvantages in using the OASIS software against other softwares like the WINNEBAGO of the International School in Makati, 3) to find out the mechanisms used by the BIS library administrators and staff in response to the changes brought by the computerization of the library, and 4) to determine how students and faculty of BIS react to the computerized library services.